Treatment of periorbital syringomas: review of scientific literature in the last 5 years - Karols Tatiana Vila Claro; Jorge Luis Hoyos Ramirez; Alessandra Haddad; Marisa Gonzaga da Cunha; Miguel Francischelli (Revista Brasileira de Cirurgia Plástica)
Introduction: Syringomas are benign adnexal tumors with histopathological characteristics arising from the eccrine ducts, in yellowish or skin-colored papules, 1-3 mm, commonly in the lower periorbital region, which can cause important cosmetic problems. The goal of treatment is to improve appearance by destroying the tumor using minimally invasive methods and including surgery. There are multiple treatment options in the literature with varying degrees of success, but little is known about their effectiveness. Complete removal is unsuccessful, and side effects have been described, recurrence being the most frequent.Methods: This is a narrative review of the literature of scientific publications in the period 2014-2019.Results: After reviewing 45 articles and identifying those published in the last five years that had a record of the number of patients, treatment description, scales of evaluation of results and follow-up, six articles were selected. Of the total number of six articles, we found: a systematic review and five retrospective studies, one being a comparative one. A number was assigned to each article analyzed, and the number of patients included, treatment performed, assessment scales and results, complications and conclusions were collected.